Age-specific Prevalence Rates of Phimosis and Circumcision in Taiwanese Boys - Ming-Chung Ko; Chih-Kuang Liu; Wen-Kai Lee; Huey-Sheng Jeng; Han-Sun Chiang; Chung-Yi Li (Journal of the Formosan Medical Association, 2007)
To estimate the age-specific prevalence rates of phimosis and circumcision in an urban sample of Taiwanese boys. Methods: A convenience sample of 1145 boys aged from 7 to 13 years was enrolled and cross-sectionally evaluated for preputial retractability and status of circumcision. Another convenience sample of 59 newborn male infants was enrolled from the infant room of a city municipal hospital. These infants were examined for preputial development at birth. Results: None of the newborn male infants had a completely retractable prepuce (i.e. type 3). The prevalence rate of type 3 prepuce increased with age from 71.7% (95% confidence interval [CI], 66.5-75.5%) for boys aged 7 years to 72.4% (95% CI, 67.3-77.0%) for boys aged 10 years and 84.1% (95% CI, 79.6-88.0%) for boys aged 13 years. In contrast, the prevalence rate of type 1 prepuce decreased with age from 83.1% (95% CI, 71.0-91.6%) for newborn infants to 0.3% (95% CI, 0.0001-1.8%) for boys aged 13 years. On the other hand, the prevalence of circumcision slightly increased with age from 7.2% (95% CI, 5.3-10.8%) for boys aged 7 years to 8.7% (95% CI, 6.5-13.3%) for boys aged 13 years. Conclusion: Nonretractability of the prepuce was very common among the Taiwanese newborns. Among the school boys, the degree of preputial separation and exposure of glans increased with age and progressed even more rapidly in adolescence. Very few boys still suffered from unretractable prepuce by the age of 13. [J Formos Med Assoc 2007;106(4):302-307]